Identification of hydrological transformations, extreme flooding events and their response of small reservoirs in the light of the studies of the Olęder pond sediments in the Middle Vistula Valley - Kultys, Kamil (Acta Geographica Lodziensia, 2021)
The study attempts to reconstruct the ecological changes recorded in the sediments of a small Olęder pond located on a flat, left-bank floodplain terrace of the Vistula River at a riverbank embraced by the Vistula and its left-bank tributary, the Zagożdżonka River. Archival cartographic materials were used to identify hydrological conditions and their changes caused by the expansion of the hydrotechnical infrastructure since the early 20th century. High-resolution analyses of biogenic sediments collected from the pond allowed the pivotal hydrological changes taking place in this part of the Middle Vistula Valley to be identified. Ecological changes have been reconstructed using palaeoenvironmental analyses, fossil remains of Cladocera, and selected microfossils. Then, these results were correlated with the stages of flood embankments expansion. The conclusions from the study show that the river embankments had a significant impact on changes in ecological conditions in the studied pond.